Application of modern information technologies as a necessary means of preventing and stopping conflict interests in the judicial activities of Russia - Ryabtseva Е.В. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article analyzes the influence of artificial intelligence on the development of justice in Russia. Taking into account the experience of foreign countries, proposals are made aimed at minimizing corruption risks in judicial activities through the use of information technology. It is substantiated that information technologies used to prevent and suppress conflicts of interest as a guarantee of the independence and impartiality of judges can become part of the ongoing digitalization of justice. As an effective way to prevent conflicts of interest, it is proposed to develop specialized programs that would help judges assess certain situations of conflict of interest and take appropriate measures aimed at preventing it. It is concluded that the system of electronic distribution of cases existing in Russia today makes it possible not to distribute to the judge those cases in which relatives and family members work, which seems insufficient to eliminate conflicts of interest when using the modern system of distribution of cases. The more clear parameters are developed for a system that provides electronic distribution of cases, the fewer situations of conflict of interest will arise. The article substantiates that the optimization of the system for managing conflicts of interest in judicial activities is directly related to information systems, the creation of a single electronic resource for the prevention of conflicts of interest, including: electronic consultation of judges on conflict of interest situations; electronic distribution of cases by excluding from consideration by the judge those whose participation entails a conflict of interest; checking candidates for the position of judge to establish the circumstances preventing their appointment.